A chameleonic macrocyclic peptide with drug delivery applications. Issue 19 (15th April 2021) - Payne, Colton D.; Franke, Bastian; Fisher, Mark F.; Hajiaghaalipour, Fatemeh; McAleese, Courtney E.; Song, Angela; Eliasson, Carl; Zhang, Jingjing; Jayasena, Achala S.; Vadlamani, Grishma; Clark, Richard J.; Minchin, Rodney F.; et al.
Abstract : The cyclic peptide PDP-23 adopts a different structure depending on conditions. In water it forms a dimer, but can unfold allowing its hydrophobic core to interact with membranes. PDP-23 shows promise as a cell penetrating scaffold for drug delivery. Abstract : Head-to-tail cyclized peptides are intriguing natural products with unusual properties. The PawS-Derived Peptides (PDPs) are ribosomally synthesized as part of precursors for seed storage albumins in species of the daisy family, and are post-translationally excised and cyclized during proteolytic processing. Here we report a PDP twice the typical size and with two disulfide bonds, identified from seeds of Zinnia elegans . In water, synthetic PDP-23 forms a unique dimeric structure in which two monomers containing two β-hairpins cross-clasp and enclose a hydrophobic core, creating a square prism. This dimer can be split by addition of micelles or organic solvent and in monomeric form PDP-23 adopts open or closed V-shapes, exposing different levels of hydrophobicity dependent on conditions. This chameleonic character is unusual for disulfide-rich peptides and engenders PDP-23 with potential for cell delivery and accessing novel targets. We demonstrate this by conjugating a rhodamine dye to PDP-23, creating a stable, cell-penetrating inhibitor of the P-glycoprotein drug efflux pump.